La aportación del análisis contextual a la exégesis de los textos bíblicos - Guijarro Oporto, Santiago, 1957- (2017)
The methodological turn that took place during the decade of the 1980s in the field of biblical exegesis enhanced the traditional perspective of historical-critical analysis by proposing a study of biblical texts from a literary and contextual standpoint. The article introduces the assumptions and method of contextual analysis, which turns to different social sciences to reconstruct the social settings of the texts. To explain such a method, the article reconstructs the reading scenario posited by the healing accounts of the Gospels.
Keywords: Biblia; Hermenéutica bíblica; Cristianismo